2021
DOI: 10.1007/s10796-021-10156-2
|View full text |Cite
|
Sign up to set email alerts
|

Questioning Racial and Gender Bias in AI-based Recommendations: Do Espoused National Cultural Values Matter?

Abstract: One realm of AI, recommender systems have attracted significant research attention due to concerns about its devastating effects to society’s most vulnerable and marginalised communities. Both media press and academic literature provide compelling evidence that AI-based recommendations help to perpetuate and exacerbate racial and gender biases. Yet, there is limited knowledge about the extent to which individuals might question AI-based recommendations when perceived as biased. To address this gap in knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 96 publications
1
24
0
Order By: Relevance
“…For example, cultural background, among other factors, was shown to play a role in individuals' justice perceptions. This supports other work such as Gupta et al (2021) who, using established cultural dimensions, provide evidence that a manager's cultural identity may impact on the extent to which they accept or question an AI-based decision. They suggest that a manager who is individualistic with low masculinity and weak uncertainty avoidance is more likely to accept a recommendation without question, compared to a manager who has a collectivist orientation with high masculinity and strong uncertainty avoidance.…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…For example, cultural background, among other factors, was shown to play a role in individuals' justice perceptions. This supports other work such as Gupta et al (2021) who, using established cultural dimensions, provide evidence that a manager's cultural identity may impact on the extent to which they accept or question an AI-based decision. They suggest that a manager who is individualistic with low masculinity and weak uncertainty avoidance is more likely to accept a recommendation without question, compared to a manager who has a collectivist orientation with high masculinity and strong uncertainty avoidance.…”
Section: Theoretical Implicationssupporting
confidence: 85%
“…XAI techniques can be used to address the emerging black box problem that characterizes modern AI models (Adadi & Berrada, 2018;Arrieta et al, 2020;Gunning & Aha, 2019;. We used XAI for justifying individual outcomes and for detecting potential errors or biases (Adadi & Berrada, 2018;Gupta et al, 2021). Research has shown that explainability features in DSSs can positively affect the users' satisfaction with the decision-making process (Li & Gregor, 2011).…”
Section: Derivation and Justification Of Design Principlesmentioning
confidence: 99%
“…Confirmation bias occurs, when users encounter information that reinforces their pre-existing beliefs and attitudes (Bessi, 2016;Geschke et al, 2019;Zhao et al, 2020). Confirmation bias is defined as the tendency to interpret, search for, recall, and favour the information in a way that confirms one's pre-existing beliefs or hypotheses resulting into polarised views about an issue or event (Westerwick et al, 2017;Gupta et al, 2021). Confirmation biases indicate why a group of individuals with opposing views on a topic can view the same evidence.…”
Section: Confirmation Biasmentioning
confidence: 99%
“…In the context of this study, social media can induce polarisation in the form of echo chambers in global supply chains due to regional differences in terms of selecting, filtering, and sorting of information on social media (Flaxman et al, 2016;Miroudot, 2020). For example, echo chambers can occur as a global event unfolds (i.e., Covid-19, natural disaster) whereby supply chain participants are influenced by their professional and personal experiences (Bhagwat & Sharma, 2007;Muckstadt et al, 2001), as well as the information that is circulated and referred through social media (Gupta et al, 2021;Barberá et al, 2015;Toubiana & Zietsma, 2017). The impact of echo chambers on supply chain decision making can lead to excessive or insufficient stock levels in regional warehouses (Sharma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%